Teachers Storying Themselves Into Teaching: Comics as an Emergent and Relational Form of Research (LEARNing Landscapes, 2018)
In this article, we explore two comics that were produced in a province-wide teacher mentorship initiative in British Columbia, Canada. Comics-based research, undertaken through a collaborative approach, underscores the potential for this kind of research to highlight teacher stories and methodologically engage in an artistic collaboration within a research team. We use this opportunity to discuss how the mentoring project brought to our awareness the importance of sharing teachers’ stories among peers, as teachers came together to study their professional practices.
Keywords: comics-based research; teacher mentorship; space of emergence